The Effect of Dietary Cholesterol on Platelet Survival in the Rabbit – A Study Using 14C-Serotonin and 51Chromium Double-Labelled Platelets - Wanless, Ian R (Thrombosis and Haemostasis, 1984)
Hypercholesterolemic men and monkeys have shortened platelet survival but attempts to demonstrate this in rabbits have been unsuccessful. The present study examines platelet survival in cholesterol-fed rabbits. Platelets were double-labelled in vitro with 51Cr and 14C-serotonin or in vivo by intravenous injection of 14C-serotonin.In the double-label experiments 51Cr survival was always shorter than 14C survival but changes in survival of one label were accompanied by similar changes in the other label. Survival was shortened after 4 and 7 weeks of cholesterol feeding. This was demonstrated when the donor platelets were from normal rabbits for both cholesterol and control recipients but no shortening was demonstrated when cholesterol-rich platelets were injected into cholesterol-fed recipients and normal platelets were injected into the control rabbits. When 14C-serotonin was injected intravenously 14C survival was the same as when platelets were labelled ex vivo prior to injection and 14C survival was shortened in rabbits fed cholesterol for 1,2, and 6 weeks.These results indicate that cholesterol-feeding shortens platelet survival. This effect may be masked if the test platelets are not identical in both test and control groups.
Keywords: Cholesterol; Rabbits; Platelet survival; Serotonin and chromium labelling